Post-Bariatric Surgery Satisfaction and Body-Contouring Consideration after Massive Weight Loss - Aldaqal, Saleh M (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Following a bariatric surgery and massive weight-loss, the outcome is usually sullied by consequences on the body's contour and redundant skin. AIMS: We aimed to record the frequency of contour irregularities and quantify patients’ satisfaction with appearance and anticipations from body contouring surgery. MATERIALS AND METHODS: The ethical committee at King Abdulaziz University Hospital approved the study, and patients were consented. A cross-sectional study targeting the post-bariatric patients from May 2011 to April 2012 was conducted at our hospital. We used post-massive weight loss Satisfaction Questionnaire. RESULTS: The total numbers of patients were 64 (51 women and 13 men), of which 57 patients (89.2%) developed sagging skin. Most patients were dissatisfied with their appearance after weight loss. The most common zones were the upper arms (50%) and abdomen (45%). Considerably more women (36.2%) than men (24%) were dissatisfied with certain body areas. The most noticeable expectation of patients from body contouring surgery was improved cosmetic appearance (65.6%) and self-confidence (64.1%). More women (70.58%) than men (46.15%) expected a better cosmetic appearance after body contouring (P = 0.003). CONCLUSION: After bariatric surgery, sagging excess skin is an unsatisfactory problem. Therefore, body contouring surgery must be included in morbid obesity management.